2020
DOI: 10.3892/etm.2020.9037
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑652 promotes cell proliferation and osteosarcoma invasion by directly targeting KLF9

Abstract: Previous studies have demonstrated that various microRNAs (miRNAs or miRs) are abnormally expressed in osteosarcoma (OS) and serve roles in its malignant development. An in-depth understanding of the specific roles of dysregulated miRNAs in OS may be important for cancer research and the identification of novel therapeutic targets. In the current study, reverse transcription-quantitative PCR was performed to determine miR-652 expression in OS tissues and cell lines. Cell Counting Kit-8 and Transwell invasion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…KLF9 is an evolutionarily well-conserved transcriptional regulator implicated as a tumor/metastasis suppressor in liver [ 24 , 25 ], endometrium [ 36 , 37 ], colon and rectum [ 38 ], breast [ 39 ], glioblastoma [ 40 ], ovary [ 41 ], and osteosarcoma [ 42 ]. Nevertheless, the underlying mechanism of its tumor-suppressive action for any given tissue remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…KLF9 is an evolutionarily well-conserved transcriptional regulator implicated as a tumor/metastasis suppressor in liver [ 24 , 25 ], endometrium [ 36 , 37 ], colon and rectum [ 38 ], breast [ 39 ], glioblastoma [ 40 ], ovary [ 41 ], and osteosarcoma [ 42 ]. Nevertheless, the underlying mechanism of its tumor-suppressive action for any given tissue remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…KLF9 is considered to be a tumor-suppressive gene, and KLF9 is downregulated in non-small cell lung cancer, breast cancer, colorectal cancer and other cancers, and KLF9 partakes in inhibiting the malignant phenotypes of cancer cells [ 52–54 ]. Moreover, KLF9 is reportedly under-expressed in OS cells and tissues and it participates in modulating the malignant progression of OS [ 55 , 56 ]. Reportedly, miR-889 targets KLF9 in non-small cell lung cancer and breast cancer cells [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human and rat atherosclerotic plaques, miR-652-3p is up-regulated and participates in its progression [ 31 ]. Osteosarcoma tissue and cell line miR-652-3p are significantly elevated and are involved in cell proliferation and migration [ 32 ]. miR-652-3p was remarkedly elevated in tumor tissue of patients with uveal melanoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA plays its specific function by regulating its target genes, so we try to explore them. Previous studies have found that Kuppel-like factor 9 (KLF9) is a potential target gene of miR-652 and participated in the regulation of proliferation and invasion of osteosarcoma by miR-652 [ 32 ]. And the role of KLF9 in HCC has been revealed to some extent in previous studies.…”
Section: Discussionmentioning
confidence: 99%